Mendel the fraud? A social history of truth in genetics. (June 2022) - Radick, Gregory
Abstract: Two things about Gregor Mendel are common knowledge: first, that he was the "monk in the garden" whose experiments with peas in mid-nineteenth-century Moravia became the starting point for genetics; second, that, despite that exalted status, there is something fishy, maybe even fraudulent, about the data that Mendel reported. Although the notion that Mendel's numbers were, in statistical terms, too good to be true was well understood almost immediately after the famous "rediscovery" of his work in 1900, the problem became widely discussed and agonized over only from the 1960s, for reasons having as much to do with Cold War geopolitics as with traditional concerns about the objectivity of science. Appreciating the historical origins of the problem as we have inherited it can be a helpful step in shifting the discussion in more productive directions, scientific as well as historiographic.